Video-rate two-photon microendoscopy using second harmonic resonance fiber scanning - Zhang K.; Ducourthial G.; Sharan T.; Mohan A.; Hou J.; Timilsina S.; Liang R.; Louradour F.; Spring B.Q. (My University, 2025)
We present a 2.5-mm-diameter resonant fiber scanning two-photon microendoscope with a 30-mm long forward-viewing rigid probe tip that enables video-rate imaging (20 Hz frame rate) suitable for hand-held imaging of tissues without motion artifacts. Higher-order harmonic oscillation scanning techniques are developed to significantly increase the frame rate compared to prior published fiber scanning microendoscopy designs while maintaining the field-of-view (∼125 µm), the optical resolution (1.2 µm lateral and 10.9 µm axial resolution, full width at half maximum), and the spatial sampling (1250 circumferential pixels per spiral × 20 radial pixels over the diameter; 210 spirals per frame, ∼4 spiral samples per resolvable pixel) compared to a traditional scan using the fundamental resonance. 3D printed mounts were created to reduce the cost and simplify the fabrication for the fiber scanner without compromising performance or stability (<0.3 µm drift over 84 hours). A custom long-wavelength (∼1.08 µm) femtosecond fiber laser is coupled into several meters of fiber to realize a flexible, hand-held device for long-wavelength multiphoton microendoscopy. © 2024 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement.